A INTER-SENTENTIAL SWITCHING IN PURNAYASA INSTAGRAM CAPTION IN 2022 - Anak Agung Gede, Martha Brawijaya (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
Code-switching is a common phenomenon in language use. When people can speak more than one language, they will combine the language and often switch the language. This study aims to find out the popular types of transcoding kind of code-switching is Inter – Sentential used by Purnayasa Instagram captions. The code-switching employed in the Instagram caption by Purnaysasa, Purnayasa’s Instagram caption, has 8,800 followers. He is an influencer and his content is his Instagram posts where he discusses aesthetic places like landscaped cafes or Balinese architectural structures which are more and more among young people, Not only can you enjoy the food you ordered, but you can also take pictures inside such a place to upload to social media such as Instagram. The method used was qualitative, with the code-switching being identiﬁed, noted, screenshot, and ﬁnally analyzed and categorized into the framework developed by Appel and Muysken ( 1987) who proposed three types of code-switching tag switching, intra-sentential switching, inter-sentential switching. And in this study, this research only discusses one of the three types of code-switching, namely the Inter-Sential Switching type. The result after analyzing Instagram captions is 10 data on the types of code Switching. Among the types of code switching, the most commonly used are Inter-Sential Switching all of the data.